Fostering academic excellence: The synergy of self-leadership, knowledge exchange, and innovative practices in higher education - Aziz, Sharul Azuwar Abdul; Abiddin, Norhasni Zainal (Edelweiss Applied Science and Technology, 2024)
This concept paper presents a comprehensive systematic literature review examining the interconnected roles of self-leadership, knowledge exchange, and innovative practices in enhancing academic performance within higher education institutions. The review synthesizes existing research to identify key themes and relationships, proposing a conceptual framework that integrates these elements. Following a rigorous protocol, including a thorough search strategy and clear inclusion criteria, the review analyzes selected studies to reveal the pivotal role of self-leadership in boosting academic staff performance through enhanced self-motivation and self-regulation. Furthermore, knowledge exchange and innovative practices emerge as crucial mediators in the relationship between self-leadership and academic excellence. The resulting conceptual framework highlights the interplay between these variables, suggesting potential pathways for higher education institutions to cultivate a culture of continuous improvement and innovation. This paper concludes by discussing theoretical and practical implications, emphasizing the need for institutions to prioritize the development of self-leadership skills, create supportive environments for knowledge exchange, and encourage innovative practices to elevate academic performance. The systematic literature review and proposed framework provide a foundation for future empirical research and offer valuable insights for academic leaders and policymakers seeking to enhance institutional effectiveness in higher education